Impact of magnetic islands on plasma flow and turbulence in W7-X. (29th July 2021) - Estrada, T.; Maragkoudakis, E.; Carralero, D.; Windisch, T.; Velasco, J.L; Killer, C.; Andreeva, T.; Geiger, J.; Dinklage, A.; Krämer-Flecken, A.; Wurden, G.A.; Beurskens, M.; et al.
Abstract: The effect of magnetic islands on plasma flow and turbulence has been experimentally investigated in the stellarator W7-X. Magnetic configurations with the 5/5 magnetic island positioned at the plasma edge, inside the last closed flux surface, are studied. The main diagnostic used in the present work is a V-band Doppler reflectometer that allows the measurement of the perpendicular plasma flow and density fluctuations with good spatial resolution. A characteristic signature of the 5/5 magnetic island is clearly detected in the perpendicular flow profile. The comparison of the experimental flow and the neoclassically driven E × B flow indicates that the island contribution to the flow is maximum at the island boundaries and close to zero at the island O-point. Besides, a reduction in the density fluctuation level is found nearby the island O-point. The similarities between these observations and those found in other devices and in gyrokinetic simulations are discussed.